ANALISIS POTENSI PAJAK DAN RETRIBUSI DAERAH KABUPATEN SLEMAN TAHUN 2006 – 2010 - Adi, Andreas Suryo; Sulistiyowati, Firma (Jurnal Ilmiah Akuntansi dan Bisnis, 2013)
ABSTRACT The research aimed to determine: the level of effectiveness of each local tax and retribution, the growth rate of each local tax and retribution, the level of contribution of each local tax and retribution toward total local taxes and retributions at Sleman Regency year 2006 – 2010 and each condition of local taxes and retributions calculated with potential matrix (whether included in the prime, potential, developing or underdeveloped category) at Sleman Regency. The type of this research was case study. The data were taken by doing interview and documentation. The techniques of the data analysis were calculating effectiveness ratio, growth ratio, contribution ratio, and potential matrix. The result of this research showed that the effectiveness level of each local tax and retribution revenue was more than 100%, but there were still four local retributions which were under 100%. The growth rate of each local tax and retribution was positive but there were three types of local retributions that were negative. The level of contributions in each tax toward local taxes were not potential but there were two kinds of local taxes that were potential, and for the local retributions, there were four local retributions which were in potential category. Excluding those four, the retributions were not potential. In potential matrix, there were two types of local taxes and four types of local retribution in prime category. Keywords:  contribution, effectiveness, growth rate, local  tax, potential matrix, retribution